Biotesting of decabromodiphenyl oxide using a multi-component test system - Erdniev, L. P.; Gusev, Yu. S.; Pleshakova, Y. V.; Kosheleva, I. S.; Kuzyanov, D. A.; Mikerov, A. N. (Povolžskij èkologičeskij žurnal, 2024)
The results of biotesting of decabromodiphenyl oxide using a multicomponent test sys- tem are presented. It has been demonstrated that its aqueous solutions exhibit a reverse dose- dependent effect in stimulating the growth of colonies of the green algae Chlorella vulgaris and show no signs of toxic effects on Daphnia magna. During the thermal decomposition of decabro- modiphenyl oxide at a temperature of 400°C, a mixture of products is formed, one of which is bromine. The decomposition product is released into the air and possesses toxic properties, as evi- denced by stimulation of the growth of colonies of the green algae Chlorella vulgaris, as well as the death and growth abnormalities of Planorbis mollusk embryos. Therefore, water samples con- taining decabromodiphenyl oxide can be assessed for toxicity by biotesting methods, using cul- tures of green algae Chlorella vulgaris and 24-hour-old Planorbis embryos as test subjects. It is noteworthy that in the context of the prevailing perception of the safety of decabromodiphenyl ox- ide, based on its poor water solubility and low toxicity to biological organisms, there arises a need to study embryotoxic effects of the thermal decomposition products on both animals and humans.